2018
DOI: 10.1016/j.chempr.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Thermodynamic and Kinetic Contributions in Expanding the Stability Window of Aqueous Electrolytes

Abstract: Aqueous electrolytes come with an intrinsic narrow electrochemical stability window (1.23 V). Expanding this window represents significant benefits in both fundamental science and practical battery applications. Recent breakthroughs made via super-concentration have resulted in >3.0 V windows, but fundamental understanding of the related mechanism is still absent. In the present work, we examined the widened window (2.55 V) of a super-concentrated (unsaturated) aqueous solution of LiNO 3 through both theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
230
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(243 citation statements)
references
References 37 publications
(45 reference statements)
12
230
1
Order By: Relevance
“…However, Zheng and co‐workers later showed that a mild temperature elevation from 25 to 35 °C immensely raises the solubility of LiNO 3 in water from 12 (as per Yamada et al.) to 22 m ,. They further showed that cheap LiNO 3 salts could be used to cycle aqueous batteries on a par with, or even better than, expensive LiTFSI‐based ionic liquids, due to a polymer‐like aggregation of Li−O−Li−… atoms, which begins at a salt‐to‐water molar ratio of 1:2.5, affording an electrolyte stability window of 2.55 V (Figure ).…”
Section: Mechanisms Steering Metal‐ion Electrochemistry In Watermentioning
confidence: 99%
“…However, Zheng and co‐workers later showed that a mild temperature elevation from 25 to 35 °C immensely raises the solubility of LiNO 3 in water from 12 (as per Yamada et al.) to 22 m ,. They further showed that cheap LiNO 3 salts could be used to cycle aqueous batteries on a par with, or even better than, expensive LiTFSI‐based ionic liquids, due to a polymer‐like aggregation of Li−O−Li−… atoms, which begins at a salt‐to‐water molar ratio of 1:2.5, affording an electrolyte stability window of 2.55 V (Figure ).…”
Section: Mechanisms Steering Metal‐ion Electrochemistry In Watermentioning
confidence: 99%
“…What's more, the toxicity and flammability of organic electrolytes have given rise to environment‐related concerns . Based on the above, aqueous electrolytes receive intensive attention due to a combination their being intrinsically safer, highly conductive, low cost and eco‐friendly . Nevertheless, the water decomposition voltage renders their operation only up to 1.23 V in theory, which is the consequence of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), near the negative and positive electrode respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the salt, main component in the highly concentrated electrolyte, inevitably increases the cost of the electrolyte, which represents a significant challenge in accomplishing the commercialization of concentrated electrolytes . Taking into account that, it is significance to explore a novel low cost water‐based electrolyte matching above prerequisites, such as some low concentrations of perchlorate, sulfate, chloride and nitrate, have been widely used for aqueous metal‐ion batteries and supercapacitors . The concentration of sodium nitrate solution with the lowest cost can reach 12 m (mol kg −1 ) among these salts possessing high solubility, which is accordance with the definition of WIS (the weight of the salt outnumbers that of the solvent) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high oxidative stability of solvents in HCE is more due to kinetic factors. Beside the passivating SEI film originating from anion oxidation, the polymer‐like chains of −solvent−cation−solvent−, induced by the electrostatic interaction between the lone pairs of solvents and the cations, are mainly attributed to the expanded oxidation stability ,. Overall, the HCEs normally exhibit higher redox stability than the conventional electrolytes, indicating that they are more suitable for DCBs.…”
Section: Highly Concentrated Electrolytesmentioning
confidence: 99%